Effects of resveratrol on postmenopausal women: a systematic review and meta-analysis - Wu, Weidong; Meng, Tianwei; Jin, Fangfang; Li, Junwei; Huang, Jiahao; Guo, Zhuang; Yu, Miao; Zhou, Yanyan (Frontiers in Pharmacology, 2025)
ObjectivesThis meta-analysis aims to systematically evaluate the impact of resveratrol on postmenopausal women.MethodsWe searched seven electronic databases and conducted meta-analyses using Stata 12.0.ResultsTen randomized controlled trials (RCTs) with 928 participants were identified. Resveratrol significantly reduced pain scores (WMD: −2.841, 95% CI: −5.631 to −0.050, p = 0.046), pain VAS scores (WMD: −7.585, 95% CI: −12.912 to −2.257, p = 0.005), PPI scores (WMD: −8.563, 95% CI: −12.866 to −4.261, p < 0.001), and CTX levels (WMD: −0.137, 95% CI: −0.204 to −0.070, p < 0.001). However, no significant effects were observed on cognition and memory (e.g., PVT, ORR, PSM, RAVLT, LSWM, FSS, DCCS, FICA, TMT), mood (depression, overall mood), metabolic parameters (glucose, insulin, HOMA-IR, triglycerides, total cholesterol, LDL-C, HDL-C), blood pressure, sleep disturbance, menopausal symptoms, SF-36 quality of life, or bone markers ALP and OC.ConclusionResveratrol may improve pain and bone metabolism (CTX) in postmenopausal women but did not affect other examined outcomes. Future large-scale trials are needed to confirm these findings and determine optimal dosing and treatment strategies.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier CRD42024566807.